Effectiveness of copper Nanoparticles addition in dental restorative adhesives on the Dental – Restoration Bond Strength : systematic review - Surianggo, Jenita; Octavia, Mora; Situmorang, Evi Ulina Margaretha (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Dental caries is the most common dental problem that can be restored overcome by composite resins. The weakness of composite resins is that they tend to shrink during polymerization, thereby increasing the risk of secondary caries formation due to the formation of nano-leakage between the tooth structure and the restoration. Therefore, additional materials are required, especially in adhesives, to strengthen the restoration and reducing the risk of secondary caries, such as adding copper nanoparticles. This study aimed to determine the effectiveness of copper nanoparticles addition on the micro – tensile bond strength (µTBS) and nanoleakage between the resin – dentin interface. Methods: Systematic study uses a research method by entering keywords in the PubMed, EBSCO, and Google Scholar databases for the 2012 – 2022 time period. This systematic study was made based on PRISMA guidelines and evaluated with JBI Critical Appraisal tools. Inclusion criteria in this study were all experimental studies under the research topic. Results: Micro – tensile bond strength (µTBS) continues to increase with the addition of copper nanoparticle concentrations up to 0.5%, because at higher concentrations CuNp acts as a plasticizer. CuNp also increases the strength of collagen network enzymes and resistance to proteolytics, thereby reducing nano-leakage. Conclusion : Copper nanoparticles addition in the dental restoration adhesive were effective in increasing the micro – tensile bond strength and decreasing nanoleakage.KEY WORDSnanoparticles, copper, composite resin, bonding agent, bond strengthEfektivitas penambahan nanopartikel tembaga dalam bahan perekat restorasi gigi terhadap kekuatan ikatan bahan restorasi dengan gigi: systematic reviewABSTRAKPendahuluan: Karies merupakan masalah gigi yang paling umum dijumpai dan dapat direstorasi dengan resin komposit. Kelemahan resin komposit adalah mudah mengalami pengerutan selama polimerisasi sehingga meningkatkan risiko terjadinya karies sekunder akibat terbentuknya kebocoran nano antara struktur gigi dengan restorasi. Hal ini memerlukan bahan tambahan khususnya dalam bahan perekat sehingga dapat meningkatkan kekuatan ikatan restorasi dan mengurangi risiko karies sekunder, salah satunya dengan penambahan nanopartikel tembaga. Penelitian ini bertujuan untuk mengetahui efektivitas penambahan nanopartikel tembaga terhadap kekuatan  ikatan resin – dentin dan kebocoran nano antara permukaan resin dan jaringan keras gigi. Metode: Jenis penelitian telaah sistematis dengan memasukkan kata kunci pada database PubMed, EBSCO, dan Google Scholar dengan rentang waktu 2012 – 2022. Telaah sistematis ini dibuat berdasarkan guideline PRISMA dan dievaluasi dengan JBI Critical Appraisal tools. Kriteria inklusi pada penelitian ini meliputi seluruh studi eksperimental yang sesuai dengan topik penelitian. Hasil: Kekuatan ikatan resin – dentin terus meningkat pada penambahan konsentrasi nanopartikel tembaga hingga 0,5%, karena pada konsentrasi yang lebih tinggi NpCu bertindak sebagai plasticizer yang dapat mengganggu keseimbangan campuran monomer. Selain itu tembaga juga berpotensi meningkatan kekuatan jaringan kolagen dan ketahanan terhadap enzim proteolitik sehingga mengurangi kebocoran nano. Simpulan: Penambahan nanopartikel tembaga (NpCu) dalam bahan perekat restorasi gigi efektif dalam meningkatkan kekuatan ikatan resin – dentin dan mengurangi kebocoran nano.KATA KUNCINanopartikel, tembaga, resin komposit, bahan perekat, kekuatan ikatan